A Qualitative Study on the Grief of People Who Lose Their Only Child: From the Perspective of Familism Culture - Zhang, Yudi; Jia, Xiaoming (Frontiers in Psychology, 2018)
Shidu is the Chinese transliteration for ‘losing an only child’, which indicates the death of the only child in the family. Shidu is a unique social phenomenon resulting from the One-Child Policy implemented in China for several decades. Shiduers are parents who have lost their only child. The grief research scholar Neimeyer (2012) argued that grief research should consider the role of different cultures in the grieving process. Familism culture is a collectivist culture that has a profound effect on Chinese society and is likely to produce a significant effect on the grieving process of shiduers; however, this effect has not yet received systematic attention in research. To explore the effect of familism culture on the grief of shiduers, we conducted semi-structured personal interviews in Beijing, China, with seven shiduers. The study results show that the effect of familism culture on the grief of shiduers includes three levels: cognition, emotion, and behaviour. These levels are reflected in a variety of relationships, including relationships with ancestors, the deceased child, the spouse, relatives, Tong Ming Ren (the Chinese transliteration of ‘people who share the same fate’), and the country. The first four types of relationships are reflections of ‘direct familism culture’, and the latter two types of relationships are reflections of ‘extended familism culture’. The relationships with the deceased child, relatives, and Tong Ming Ren are mainly supportive; the relationship with ancestors is mainly stressful; the relationship with the spouse has a dual nature; and the relationship with the country is contradictory. Over time, shiduers have abandoned the concept of familism culture and have moved towards reducing stress and increasing supportiveness. Psychological professionals, social workers, and government staff may refer to the results of this study to help shiduers obtain support and reduce stress from the described relationships. Specific suggestions are provided in the text.